Overview of PNM Mekaar's Development in Improving Community Economic Prosperity in Pauh District, Padang City - Angriani, Wiwit; Wisroni, Wisroni (Universitas Negeri Padang, 2023)
The background of this research is the success of members in opening and developing businesses. This study aims to: 1. See the describtion of guidance in the construction of PNM Mekaar in the Economic walfare of the community in Pauh Padang district, 2. See the description of the development in the economic walfare of the community in Pauh Padang district, 3. See the description of supervision in the guidance of PNM Mekaaar in the economic welfare of the community in Pauh Padang District. The study uses a quantitative approach, with a descriptive type. The data analysis technique uses the percentage formula. The research population was 30 study residents and a sample of 67%, namely 20 people. The sampling technique used is simple random sampling. Technique in collecting data using questionnaires and data collection tools in the form of a list of statements. The result of the study found that: (1) The description of guidance in construction of PNM Mekaar in the economic welfare of the community in Pauh Padang distrit was categorized as good, (2) The description of development in the construction PNM Mekaar in the economic welfare of the community in Pauh Padang district is categorized as good, (3) The description of supervision in construction PNM Mekaar in the economic welfare of the community in Pauh Padang district is categorized as good. Suggestions are expected for further researchers to be able to innovate by researching new variables so that they can add and multiply exixting variables.Keywords: constructions, walfare